Multiple lineages of lice pass through the K–Pg boundary - Smith, Vincent S. (The Royal Society, 2011)
For modern lineages of birds and mammals, few fossils have been found that predate the Cretaceous–Palaeogene (K–Pg) boundary. However, molecular studies using fossil calibrations have shown that many of these lineages existed at that time. Both birds and mammals are parasitized by obligate ectoparasitic lice (Insecta: Phthiraptera), which have shared a long coevolutionary history with their hosts. Evaluating whether many lineages of lice passed through the K–Pg boundary would provide insight into the radiation of their hosts. Using molecular dating techniques, we demonstrate that the major louse suborders began to radiate before the K–Pg boundary. These data lend support to a Cretaceous diversification of many modern bird and mammal lineages.